Casson fluid flow over a vertical cone with non-uniform heat source/sink and high order chemical reaction (Journal of Naval Architecture and Marine Engineering, 2015)
The present investigation deals with the study of unsteady, free convective Casson fluid flow over a vertical cone saturated with porous medium in the presence of non-uniform heat source/sink, high order chemical reaction and cross diffusion effects. The numerical computation for the governing equations has been performed using an implicit finite difference method of Crank-Nicolson type. The influence of various physical parameters on velocity, temperature and concentration distributions is illustrated graphically and the physical aspects are discussed in detail. Results indicate that temperature dependent heat source/sink plays a vital role on controlling the heat transfer however the surface-dependent heat source/sink also has notable influence on the heat transfer characteristics. It is to be noted that high order chemical reaction has the tendency to dilute the influence of chemical reaction parameter on the species concentration.